Rancang Bangun Purwarupa Pengendali Relay Menggunakan Mikrokontroler Arduino Berbasis Internet of Things - Ilham Ilham; Asruddin Asruddin; Joko Saputro (FIKOM Universitas Bung Karno, 2023)
Electricity is one of the essential needs for human life, as almost every activity humans engage in involves the use of electric energy. The advancement of technology in the field of computers has enabled humans to have a forward-thinking mindset in the application of electronic devices. The development of sophisticated technology that can remotely control household electronic devices such as lights using the Internet of Things (IoT) aims to save electrical energy used in each home. IoT serves as a transmission medium for embedded computing devices that are individually identified within the internet infrastructure. The control system in this research is designed through the relay circuit control method using the Arduino ATmega328 microcontroller as the central control unit of the system. It is supported by the ESP8266 WiFi module, which functions as a communication tool between the microcontroller and the wide-ranging interconnection network via WiFi, collaborating through a user interface design for an Android-based application.